Cross-language perception and production of stops and fricatives among Malay and Hausa native speakers - Abdullahi, Jamilu (2018)
This thesis presents results of a collection of studies that focuses on the production and perception of plosives, implosives, and fricatives by native speakers of Hausa and Malay. Selections of stops and fricatives were chosen from these two languages as they provided controls for interpretations of the analysis. Implosives are found in Hausa but not in Malay, and likewise specific stops and fricatives are found in Malay but not in Hausa. The first objective focuses on the production of stops and acoustic analysis of plosives and implosives by two groups of native speakers. The acoustic comparison would bring a further understanding of acoustic cues that are related with voiced plosives and voiced implosives. This will help in investigating the perception and production difficulties of the plosives and implosives. A total number of 45 Hausa native speakers and 45 Malay native speakers were recruited to participate in the study. All the participants were given a set of words consisting of the different combination of the target sounds to produce. PRAAT (Boersma & Weenink, 2001) was used to acoustically analyse all the recordings. In particular, voice onset time (VOT) and closure duration (CD) was measured for all the target consonants. The findings also showed that VOT is a distinctive feature that distinguishes place of articulation for various classes of plosives but it does not discriminate plosives from implosives. Instead, CD is a more reliable acoustic cue to differentiate between voiced plosives and voiced implosives. The result also show that the universal VOT categories (i.e. prevoicing, short voicing lag, and long voicing lag) are not refined enough to account for differences between plosives and implosives. The second objective focuses on the discrimination of non-native fricatives and implosives. The study examined cross-language perception of stops (/ɓ/, /ɗ/, /b/, /d/, /p/, /t/) and fricatives (/f/, /v/, /z/, /t/, /s/) among Hausa speakers who have little exposure to Malay and Malay native speakers who have no exposure to Hausa. This study functions as the base-line for interpretation of the third study where imitation of a presented stimuli becomes the focus. Audio-recording of Malay and Hausa words (minimal pairs) were used as stimuli. The target sounds (stops and fricatives) were at the initial positions of each pair of words and were presented in an AX discrimination task. The results revealed that the Malay and Hausa native speakers faced considerable difficulties and problems in perceiving most non-native sounds contrasts. The third objective focuses on the production of non-native fricatives and implosives. The Hausa native speakers were asked to produce Malay fricatives while the Malay native speakers imitated Hausa voiced implosives. Their productions were recorded and analyzed by getting native raters to rate the accuracy of the production. The results showed that the Hausa native speakers often substituted the fricatives with plosives /p/ and /b/ sounds. Similarly, the Malay native speakers were unable to imitate the implosives correctly.